Proceedings of the 33rd Annual ACM Symposium on User Interface Software and Technology 2020
DOI: 10.1145/3379337.3415872
|View full text |Cite
|
Sign up to set email alerts
|

Authr

Abstract: Model current task Collaboratively perform task Allocate steps to human and robot Figure 1. We present a novel workflow and a software environment, called Authr, that enable engineers to translate single-person, work-related tasks in domains ranging from manufacturing to logistics into tasks that can be performed by human-robot teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…The efficient allocation of tasks between human workers and collaborative robots is also an important consideration. Several studies have been conducted on optimal task allocation (Kwon & Suh, 2014; Schoen et al, 2020; Tsarouchi et al, 2017). Optimal task allocation can affect task efficiency because human workers have the advantage of being flexible and creative, whereas robots have the advantage of being able to perform repetitive and precise tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The efficient allocation of tasks between human workers and collaborative robots is also an important consideration. Several studies have been conducted on optimal task allocation (Kwon & Suh, 2014; Schoen et al, 2020; Tsarouchi et al, 2017). Optimal task allocation can affect task efficiency because human workers have the advantage of being flexible and creative, whereas robots have the advantage of being able to perform repetitive and precise tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The second decision was whether a feasible algorithm existed to handle the logic behind the non-static work activity. Such algorithms may include problem space search, neural networks, and machine learning (Andrychowicz et al, 2020; Thomas et al, 2018) or planning (Pearce et al, 2018; Schoen et al, 2020). Work activities for which there is no feasible algorithm (e.g., Job 6’s Researching Product Safety ) are rated as Low , while work activities that have such an algorithm (e.g., Job 9’s Monitor equipment fluid levels ) continue down the tree.…”
Section: Methodsmentioning
confidence: 99%
“…Pearce et al (2018) found that there were trade-offs in assigning different priorities to time and ergonomics, including completion time, total strain, and worker idle time. A simplified bi-objective approach by Schoen et al (2020) assisted engineers in constructing human-robot collaborative task plans. While the interface and approach showed clear benefits for integrating optimization in the task planning process, the formulation of human and robot cost measures were left mostly to the discretion of the engineer, who may or may not have expertise in ergonomics.…”
Section: Introductionmentioning
confidence: 99%
“…At any point during the creation of a goal automaton, end users may view the branching plan computed by Polaris within the Plan Visualizer interface. The Plan Visualizer draws from existing "timeline" interfaces in HRI [48,49] in that it displays one branch of the plan at a time from left to right, and within a horizontal scrollable pane overlaying the semantically labeled map. Initially, the plan is displayed up to when a conditional is encountered.…”
Section: Viewing the Branching Planmentioning
confidence: 99%